Immune cells and tryptophan metabolism in the joint capsule tissue in rheumatoid arthritis - E. A. Stepanov (Acta Biomedica Scientifica, 2024)
To the present day, many links in the pathogenesis of rheumatoid arthritis remain unclear, which leads to unsatisfactory results in its therapy.The aim. To study the cells involved in immune reactions and tryptophan metabolites in the joint capsule in rheumatoid arthritis.Materials and methods. The experiments were carried out on 40 Wistar rats. Rheumatoid arthritis was induced by intraperitoneal injection of a solution of type 2 collagen (Chondrex Inc., USA) in incomplete Freund’s adjuvant. On the days 7, 14 and 21, the content of tryptophan, kynurenine, 3-hydrokenurinine, L-5-hydrotryptophan in the joint capsule was determined using high-performance liquid chromatography. Cells with CD3, CD20 and CD68 in joint tissues were studied at the same time using the streptavidin-biotin-peroxidase method. We used enzyme-linked immunosorbent method to determine antibodies to citrulline-containing peptide. Statistical analysis was performed using the Jamovi, version 2.3 software.Results. The content of cells carrying CD3, CD20 and CD68 markers in the joint was high in experimental rheumatoid arthritis. In joint tissues, the content of tryptophan metabolites along the kynurenine pathway also increases and the concentration of metabolites along the serotonin pathway decreases. Direct positive correlations of cells carrying CD3, CD20 and CD68 differential clusters with the content of tryptophan metabolites along the kynurenine pathway and negative correlations with metabolites of the serotonin pathway were established.Conclusions. Cells carrying CD3, CD20 and CD68 markers and tryptophan metabolites – kynurenine and L-5-hydrotryptophan – play an important role in the pathogenesis of rheumatoid arthritis.